CORE STABILITY EXERCISE LEBIH BAIK MENINGKATKAN AKTIVITAS FUNGSIONAL DARI PADA WILLIAM’S FLEXION EXCERCISE PADA PASIEN NYERI PUNGGUNG BAWAH MIOGENIK - Pramita, Indah; Pangkahila, Alex; -, Sugijanto (Sport and Fitness Journal; Volume 3, No.1, 2015, 2015)
Myogenic low back pain is pain around of the lower back mucle caused by disorder or abnormalities in the elements of muscles and tendons without neurological disorders. Myogenic low back pain may result in pain, muscle spasm and muscle imbalance, so that the stability of abdominal muscles and low back decreased, lumbar mobility is limited, resulting in a decrease in functional activity. The exercise was usually given in a hospital Short Wave Diathermy combined with William's Flexion Exercise (WFE). The existence of a new method of core stability exercise (CSE) is very important for patients with myogenic low back pain. CSE was function to activate the harmonious movement between the four core muscle groups. The activation of these four core muscles will given stability on the lower back. The purpose of this study to determine core stability exercise is better than William's Flexion Exercise increases the functional activity in patients with myogenic low back pain. This study uses a quasi experimental design with pre-test and post-test control group design. The experiment was conducted in a clinic in Denpasar. Subjects were 28 patients who fulfill the criteria were established of the researchers. The increasing of functional activity was measured with the Oswestry Disability Index (ODI) before and after training. Subjects were divided into two groups, they are the treatment group was given SWD and CSE three times a week and a control group given SWD and WFE three times a week. The results of statistical test was obtained, occur of decreasing in ODI scores in the first group with p = 0.001 and in the second group with p = 0.001. It means that the first group and the second group alike can increase the functional activity significantly. From the comparative test data by t-test using the difference data in the two groups was obtained the value p=0.001, which means significantly. The difference mean value ODI in first group as 28,86% although the difference ODI in the second group as 15,41%.  From the results of the research can be concluded that the core stability exercises is more increase the functional activity than William's Flexion Exercise in patients with myogenic low back pain. The study is expected to be beneficial in patients with myogenic low back pain to improving functional activity.
Keywords: : core stability exercise, William' s Flexion Exercise, SWD, myogenic low back pain, ODI